Про процесуальні чинники підвищення авторитету судді та суду (на прикладі господарського судочинства) - Подцерковний, Олег Петрович; Подцерковный, Олег Петрович; Podcerkovnyj, Oleg (My University, 2011)
The article is devoted to remedial measures to improve the credibility of the economic courts and judges. Made a number of proposals to the Economic Procedure Code and the Code of Administrative Offences involving the expansion of powers of the courts, the introduction of property qualifications for appealing decisions of the appellate and cassation, increasing liability for contempt of court.
Подцерковний О. П. Про процесуальні чинники підвищення авторитету судді та суду (на прикладі господарського судочинства) / О. П. Подцерковний // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 113-123.
Keywords: господарські суди; повноваження судів; Господарський процесуальний кодекс; хозяйственные суды; полномочия судов; Хозяйственный процессуальный кодекс; economic courts; powers of courts; Economic Procedural Code